Washington View: What's on the horizon?. (March 2018) - Ferguson, Maria
Maria Ferguson suggests that implementation of the Every Student Succeeds Act, school choice, and career technical education will dominate the conversation about education policy in 2018. On the other hand, school funding inequities, as discussed at length in a recent report from the U.S. Commission on Civil Rights, deserve more attention than they are likely to receive .